Isostructural iron(iii) spin crossover complexes with a tridentate Schiff base-like ligand: X-ray structures and magnetic properties. Issue 41 (17th April 2019) - Dankhoff, Katja; Weber, Birgit
Abstract : Two isostructural iron(iii ) spin crossover complexes show anion-size dependent spin crossover. Abstract : Here we present two isostructural iron(iii ) spin crossover complexes with the same tridentate ligand and perchlorate or tetrafluoroborate as counter ion. Single crystal X-ray structures in the high spin and low spin state were obtained for both complexes. An abrupt spin transition above 100 K is observed with the transition temperature depending on the size of the anion.